Avaliação de desempenho operacional de microgeração e minigeração solar fotovoltaica em edificação comercial, industrial, residencial e pública no Estado do Pará - MONTEIRO, Weslley Leão (Universidade Federal do Pará, 2024)
This work evaluates the operational performance of different Photovoltaic Systems Connected to the Electric Grid, installed in 5 (five) consumer units, four in the metropolitan region of Belém/PA and one in Santarém/PA, consumption class: Residential, Commercial, Industrial and Public, in order to contribute to the construction of scientific knowledge and make public performance values of photovoltaic generators connected to the conventional grid in the North region of the country. For this, the electricity production data provided by the online monitoring platform of the grid connection inverter of each SFCR, in the years 2019 to 2021, was considered for the calculation of the merit indexes. monitoring, the data presented on the inverter display was considered. To calculate the final yield (YF) of two systems, the value of the real power of the photovoltaic generator was considered through I-V curve tests carried out in real sun with a curve tracer (Solar IVe) provided by GEDAE/UFPA, considering measurements performed in an arrangement of a subsystem. For the estimated performance ratio calculation, the Meteonorm v8.0 database was considered to obtain irradiation in the GFV plane. The results obtained in this work allow comparing the estimated global performance of the systems, making it evident that the operational results are directly related to the solution implemented in each system, to good practices during installations, and the importance of a more rigorous and continuous control of the SFCR monitoring.